Pengaruh Kampanye Ingat Pesan Ibu terhadap Sikap Patuh Protokol Kesehatan pada Masyarakat Kabupaten Karawang - Zalfa Salsabila Aulia Putri; Christin, Maylanny (Fakultas Ilmu Komunikasi Universitas Islam Riau, 2022)
In the midst of the Covid-19 pandemic that is currently spreading, the government is intensifying actions so that the Indonesian people are obedient in implementing the Covid-19 prevention health protocol. One such action is to intensify the